Taxonomic notes on Dutch desmids VII (new species, new names, new record) - Coesel, Peter; Meesters, Koos (Phytotaxa, 2015)
From the Netherlands, Cosmarium bipyrenoideum and Euastrum spondylosioides were described as new to science. Cosmarium laeve var. distentum was raised to Cosmarium distentum, whereas Cosmarium cataractarum was newly reported for the Dutch flora. All four species were discussed for possible affiliations with other desmid taxa.